Kết quả nghiên cứu chọn lọc giống đậu tương AK.06 - Mai, Quang Vinh (2011)
Tác giả: Mai Quang Vinh, PGS.TS; Đỗ Minh Nguyệt; Ngô Quang Thắng; Hoàng Minh Tâm, TS; Trần Đình Đông, TS -- Từ khóa: Đậu tương